2016
DOI: 10.1002/jobm.201600323
|View full text |Cite
|
Sign up to set email alerts
|

Potential biocontrol actinobacteria: Rhizospheric isolates from the Argentine Pampas lowlands legumes

Abstract: Control of fungal plant diseases by using naturally occurring non-pathogenic microorganisms represents a promising approach to biocontrol agents. This study reports the isolation, characterization, and fungal antagonistic activity of actinobacteria from forage soils in the Flooding Pampa, Argentina. A total of 32 saprophytic strains of actinobacteria were obtained by different isolation methods from rhizospheric soil of Lotus tenuis growing in the Salado River Basin. Based on physiological traits, eight isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 39 publications
(56 reference statements)
3
7
0
Order By: Relevance
“…Specifically, host plants showed significantly less root and crown rot, and were healthier overall (El-Tarabily et al, 2009). A number of other studies have shown similar results, in various plant systems, where root-inoculated actinomycetes were able to protect the plant from harmful pathogen invasion (Xue et al, 2013; Nabti et al, 2014; Solans et al, 2016). In a notable example, Streptomyces lividans was shown to produce prodiginines on the roots of Arabidopsis thaliana , which antagonized the particularly damaging fungal pathogen Verticillium dahlia (Meschke et al, 2012).…”
Section: Actinomycete Specialized Metabolism In the Rhizospheresupporting
confidence: 58%
“…Specifically, host plants showed significantly less root and crown rot, and were healthier overall (El-Tarabily et al, 2009). A number of other studies have shown similar results, in various plant systems, where root-inoculated actinomycetes were able to protect the plant from harmful pathogen invasion (Xue et al, 2013; Nabti et al, 2014; Solans et al, 2016). In a notable example, Streptomyces lividans was shown to produce prodiginines on the roots of Arabidopsis thaliana , which antagonized the particularly damaging fungal pathogen Verticillium dahlia (Meschke et al, 2012).…”
Section: Actinomycete Specialized Metabolism In the Rhizospheresupporting
confidence: 58%
“…Other mechanisms, in addition to siderophores production by fluorescent pseudomonads, were reported that may help in suppressing and controlling fungal pathogens, such as the production of antifungal compounds and lytic enzymes. Solans et al, 2016 studied the role of siderophores as biocontrol agents [50] whereas Arya et al, 2018 revealed that tomato seedlings inoculated with P. fluorescens strains SPs9 and SPs20, which are able to produce siderophores in the soil infected with F. oxysporum, succeeded in controlling wilt disease with high efficiency [5]. Leeman et al, 1996 reported that siderophore-producing P. fluorescens induced systemic resistance against Fusarium wilt of radish [51].…”
Section: Discussionmentioning
confidence: 99%
“…MM136; MM140; MM141; MM145 and MM147. The strains were selected from a larger collection for their PGPR traits such biological N fixation in NFb, IAA, and siderophore production, exoprotease and phospholipase activities, antifungal effect and P solubilizing in NBRIP agar with Ca 3 PO 4 (unpublished data). These isolates were deposited in GenBank under the following accession numbers: KX530965, KX530966, KX530967, KX530968, and KX530970 for Streptomyces spp.…”
Section: Methodsmentioning
confidence: 99%
“…These isolates were deposited in GenBank under the following accession numbers: KX530965, KX530966, KX530967, KX530968, and KX530970 for Streptomyces spp. MM136, MM140, MM141, MM145, and MM147, respectively .…”
Section: Methodsmentioning
confidence: 99%